The geology of a portion of the country between Witvlei and Omitara, South West Africa - Fey, P (Rhodes University, Faculty of Science, Department of Geology, 1972)
A brief account of the location and physical aspects of the region is followed by descriptions of mapping and laboratory techniques employed. Recent ideas on regional stratigraphical correlation in South West Africa are critically reviewed. Strata lying southeast of the farm Losberg 105 have, on the basis of lithology and copper mineralisation, been correlated with the Tsumis Formation. The Hasib Formation, of predominantly marine character, has on structural grounds been excluded from the Damara System. The latter here has a greater thickness than elsewhere in South West Africa, unless isoclinal folding is much more prevalent than has been assumed. The occurrence on Eintracht 118 of a pebble conglomerate, tentatively equated with the Chuos Tillite, makes possible a subdivision of the Damara strata into the various series established in the literature. It has been found possible to differentiate between Kamtsas and Damara quartzites on petrological grounds. Further, it is concluded that the bulk of Hakos carbonate rocks originated as dolomites and have subsequently been dedolomitized to a greater or lesser extent. The area contains both ortho- and para-amphibolites, as well as one occurrence of intrusive granite. Evidence is given for at least three periods of deformation. It is oonsidered that, if the Hosib Formation was involved in a pre-Damara orogenic episode, later folding must have been co-axial with this. Sedimentation and metamorphism are treated in broad outline. There appears to have been a deepening of the basin of deposition from Hasib to Damara times. Cyclicity in sedimentation is evidenced by lithological associations in the Damara strata. The entire area falls into the greenschist facies of regional metamorphism. Superficial deposits include river gravel and, silt, quartzite- and vein quartz-rubble, calcrete and Kalahari sand. The economic geology is described with special reference to the widespread copper mineralisation.
Keywords: Petrology -- Namibia; Stratigraphy -- Namibia; Mineralogy -- Namibia; Geology -- Namibia